How much information of concurrency can be got from firing sequences in petri nets - Ban, Đoàn Văn; Hung, Dang Van (Journal of Computer Science and Cybernetics, 2016)
It is well known from [2, 3] that in general processes in Petri nets are not recoverable from firing sequences. However, firing sequences in Petri nets say something about concurrency. The paper presents a way to define concurrency from firing sequences of nets. It turns out that the information of concurrency in a firing sequences characterizes all its processes.